The temporal relationship between the neural and vascular actions of kallidin within the nose - K. Rajakulasingam; L. C. K. Lau; R. Polosa; M. K. Church; S. T. Holgate; P. H. Howarth (Mediators of Inflammation)
The time course of effect of the B2-receptor agonist kallidin (K) on induced changes of nasal airflow, rhinorrhoea, nasal pain, sneezing and nasal microvascular leakage has been examined and compared with its B2 metabolite agonist bradykinin (B) and the B1-agonist [des-arg9]-bradykinin (D). When administered as a single dose K and B induced an immediate sensation of pain, rhinorrhoea, elevations in lavage albumin and protein levels and a sustained increase in nasal airways resistance (NAR) for 5–40 min post-challenge. [des-arg9]-Bradykinin and vehicle placebo (V) were without effect on any of these indices. These studies identify the action of K and B within the nose and differentiate the neural and vascular effects of these kinins in addition to suggesting the potential that nasal blockage and nasal microvascular leakage represent alterations in differing vascular compartments. These findings have implications for the understanding and therapeutic manipulation of rhinitis.